BENTUK PENYAJIAN TARI GALOMBANG KATO SEPAKAT DALAM ACARA ALEK BABAKODI KOTO TANGAH KOTA PADANG SUMATERA BARAT - Aisyah Mail Nexsi; Herlinda Mansyur (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to identify and describe the Presentation Form of the Galombang Kato Sepakat Dance in the Alek Babako event in Koto Tangah, Padang City, West Sumatra. This type of research is qualitative with a descriptive approach. The research instruments include the researcher themselves, supported by writing tools and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps for analysing the data are data collection, data reduction, data processing, and drawing conclusions. The results of the research show that the form of the Presentation of the Galombang Kato Sepakat Dance in the Alek Babako event consists of movements, dancers, floor design, makeup and costumes, props, music, and the performance venue. The Tari Galombang Kato Sepakat has 4 types of movements which are: Gerak Sambah, Gerak Tari, Gerak Perkelahian, and Gerak Damai. The floor pattern consists of horizontal and vertical lines with various facing directions. Tari Galombang Kato Sepakat is performed by 8 dancers, 4 waiting dancers and 4 approaching dancers, with a duration of around 4 minutes and 14 seconds. The accompanying music for this dance uses traditional musical instruments from the Koto Tangah area, namely, pupuik batang padi, gandang duo, giriang-giriang, and talempong pacik. Tari Galombang Kato Sepakat employs props made from rattan sticks which are adorned with two-colour oil paper, as well as using a very sharp genuine German knife. The costumes used are black silek costumes with an additional songket cloth at the waist and deta cloth on the dancers' heads. The dancers in this performance do not wear makeup as they portray either a man or an aide.